THE DYNAMIC SURVIVAL OF PESANTREN IN INDONESIA A BRIEF EXPLANATION FOR DEVELOPMENT OF THE TRADITIONAL MUSLIM EDUCATION - Mahmud Arif; Siti Fatonah; Abda Billah Faza MB (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
After the ratification of Pesantren's Law, the existence of pesantren (Islamic boarding school) more be recognized as an integral part of the national education system. Historically, it has much uniqueness. In the modern era, its dynamics in Indonesia faced problematic situations: the pressure of the colonizers and the modernization of the educational system that provide disadvantages. Also, the decline of the centers of Islamic culture has residues. On one side, such situations force pesantren to take extra careful steps to look less agile in reforming its educational and institutional system in the context of the fulfillment of its traditional functions. On the side, the tradition of Islamic science developed is deemed to be very close to the Sufistic-juristic inclination that belongs to the non-puritan school. As the penetration of the modernization in the national education system is gradually accepted, its dialectical pattern has pushed pesantren to take the convergent process that makes this institution to compete as an educational institution and education provider as well.